Om Smitsom Kastning med særlig Henblik paa Bekæmpelse i større Besætninger. - Bendixen, H. C. (Tidsskrift for Landøkonomi, 2018)
Om Smitsom Kastning med særlig Henblik paa Bekæmpelse i større Besætninger.